Association of genetic markers with the efficiency of tocilizumab treatment for rheumatoid arthritis - Irina Anatolyevna Guseva; E Yu Panasyuk; N E Soroka; A S Avdeeva; E N Aleksandrova; E L Luchikhina; E E Gubar; E V Fedorenko; T N Gavva; E S Tsvetkova; E Yu Loginova; E Yu Samarkina; et al. (Научно-практическая ревматология)
Objective: to study the association of polymorphic variants of the genes playing a pivotal role in the processes of inflammation with the efficiency of tocilizumab (TCZ) therapy in patients with active rheumatoid arthritis (RA). Subjects and methods. The investigation enrolled 43 patients with active RA resistant to standard therapy with disease-modifying antirheumatic drugs who had previously received no genetically engineered biological agents. The patients received 6 intravenous infusions of TCZ in a dose of 8 mg/kg at 4-week intervals. DAS28 was used to evaluate the efficiency of TCZ therapy. Polymorphisms in the genes of interleukin 6 (IL-6) (-174G/C), IL-6 receptor (IL-6R) (+358A/C), tumor necrosis factor-а (TNF-а) (-308A/G), IL-10(-592A/C, -1082A/G), TNF^-Induced protein 3 - TNF-αIP3 T/C (rs675520), TNF-αIP3A/G (rs6920220), monocyte chemoattractant protein 1 - МСР1 (+2581A/G) were detected by a real-time polymerase chain reaction assay using fluorescently-labeled specific hybridization primers, followed by melting curve estimation by means of a DT-96 detecting amplifier (ZAO «Scientific Production Firm DNA-Technology», Russia). Results. Logistic regression analysis revealed that a therapeutic response to the first TCZ infusion was associated with the polymorphism of the TNF-а (-308A/G) gene; the odds ratio (OR) was 8.0 [95% confidence interval (CI) 1.2-52.8] (p = 0.03). The carriers of the GG genotype demonstrated a less marked response than those of the AG genotype (the AA genotype was not found). After the sixth TCZ infusion, there was an obvious trend towards a statistically significant correlation of the clinical response with the polymorphism of the TNF- аIP3 A/G (rs6920220) gene (OR = 5.5; 95% CI 0.9-32.6; p = 0.06). A good response was more frequently observed in the carriers of the homozygous GG genotype than in those of the AA/AG genotypes (68.6 and 31.4%, respectively) and, conversely, a moderate response was more common in the carriers of the AA/AG genotypes than in those with the GG genotype (71.4 and 28.6%, respectively; p = 0.06). The same polymorphism in the logistic regression analysis was identified as a prognostic marker for clinical remission (OR = 4. 2; 95% CI 1.1-16.7; p = 0.04). Conclusion. The therapeutic response to the first and sixth TCZ infusions was associated with the TNF-а and TNF-αIP3 genes playing a significant role in the activation and regulation of the nuclear factor kB (NF-kB) signaling pathway.